EVALUATION OF POTENTIAL UTILIZATION OF SEA SAND IN LONTAR VILLAGE, KOTABARU REGENCY AS FINE AGGREGATE IN CONCRETE - Taufik, Muhammad; Nurwidayati, Ratni (Universitas Lambung Mangkurat, 2023)
Not all areas have sufficient resources for concrete needs. Coastal areas are areas that are difficult to obtain suitable sand for concrete needs. One of these coastal areas is Lontar Village, Kotabaru Regency, because of this, the people of Lontar Village, Kotabaru Regency, choose to use sea sand as a concrete material. The use of sea sand in Lontar Village, Kotabaru Regency is not subject to any treatment even though sea sand has a high salt content and uniform and fine grains, this can reduce the strength of the concrete. In this study, several treatments were carried out, namely no treatment, washing treatment and flush treatment, and using percentage variations of 0%, 30%, 50%, 70% and 100% sea sand. The parameters reviewed in this study were the compressive strength of concrete, split tensile strength of concrete and flexural strength of concrete.Concrete mix planning follows SNI 7626-2012. With untreated sea sand as a control, the sea sand treatment was followed by washing and flushing to reduce the salt content in the sea sand. Using several percentages of sea sand to add variety to the grain of sea sand. The treatment method used is fresh water immersion. The sample used was a mortar mixture in the form of a cube of 5 cm x 5 cm x 5 cm, and a concrete mixture in the form of a cylinder of 15 cm x 30 cm and a beam of 50 cm x 10 cm x 10 cm.The results showed that the highest compressive strength of mortar was in 30% sea sand washing treatment with 29.71 MPa. The highest compressive strength of concrete is at 0% sea sand with 20.38 MPa. The highest split tensile strength of concrete is at 30% sea sand with 1.92 MPa. And the highest flexural strength of concrete is at 30% sea sand with a flexural force of 3.05 MPa. Keywords: Sea Sand, Compressive Strength, Split Tensile Strength, Flexural Strength.